Dona Teresa Cristina e os rastros de memória: entre a invenção da Mulher-Monumento e a escrita de si - Félix, Rodrigo da Silva (2014)
We start our work with discussions about the relations between memory and history, taking Dona Teresa Cristina Maria, the last Brazilian Empress, as a reference. By the traces memory leaves, we can see people are fragile, complex and contribute to the invention of memory. In the case of Dom Pedro II‟s wife, we have the imagery about Brazilian women in the XIX century and the many narratives about Teresa Cristina, which helped her become a Woman Monument in Brazilian History, as a background. We also take into account the elements which made her be forgotten. In this way, we think of the Empress‟s writing about herself, alluding to the practice of writing journals and letters among women. We think the figure of Dona Teresa Cristina Maria, represented in Brazilian historiography, remains as the representation of the good mother of Brazilian people , as her intimate archive suggests a woman whose image she has of herself is made between the public and the private domains.